The Pakistan trap - Sharma, Rajeev, 1959- (New Delhi : UBS Publishers' Distributors, 2001)
Pakistan's foreign relations with India; contributed articles.
Includes bibliographical references and index.
Keywords: Pakistan -- Foreign relations -- India; India -- Foreign relations -- Pakistan